COLEOPTERA DE LA RESERVA NACIONAL RIO CLARILLO (CHILE CENTRAL) CAPTURADOS CON TRAMPA MALAISE - Solervicens, Jaime; González, Christian (Acta Entomológica Chilena, 2022)
A study of the Coleóptera from the Río Clarillo National Reserve, Central Chile, was carried on. The sampling period was conducted from October 1988 to October 1989 with an aditional sampling between January and April 1990. The sampling method employed was a Malaise trap. 41 families and 205 species were collected showing a great species diversity; however only 10 species are relatively abundant and constant. Springtime showed the more abundance and diversity of Coleóptera. The similarity between samples showed seasonal associations. Springtime and summer samples were associated with their respective samples the two periods of study proving the repetition of a seasonal sequence of events.